1989
DOI: 10.1021/la00085a017
|View full text |Cite
|
Sign up to set email alerts
|

Binding of polyelectrolytes to oppositely charged ionic micelles at critical micelle surface charge densities

Abstract: The interaction of ionic/nonionic surfactant micelles with strong polyelectrolytes has been studied by turbidimetric titrations. There exists a critical micellar fraction of ionic head groups, Yc, below which no interactions can be detected. At Y > Yc, the solute components form either soluble aggregates, complex coacervate, or amorphous precipitate, depending, in part, on the polymer:surfactant stoichiometry. The dependence of Yc on the square root of the ionic strength, P/2, appears as a linear phase boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 0 publications
10
110
0
Order By: Relevance
“…3. In the presence of TMAC, we find the same linear dependence of Y c on I 1/ 2 as revealed in previous studies on a number of polyelectrolyte-micelle systems (9,11,53). This linearity suggests that the phenomenon is governed by Eq.…”
Section: Resultssupporting
confidence: 88%
“…3. In the presence of TMAC, we find the same linear dependence of Y c on I 1/ 2 as revealed in previous studies on a number of polyelectrolyte-micelle systems (9,11,53). This linearity suggests that the phenomenon is governed by Eq.…”
Section: Resultssupporting
confidence: 88%
“…An important consequence of theory 8,9 is the finding of a transition from bound to unbound state with a change in any of those three variables, so that the critical conditions for binding at constant temperature could be expressed as a result initially obtained for polyelectrolyte adsorption onto flat surfaces, but subsequently found for spherical colloids as well, 9,10 with values of b ranging from 0.5 to 3. [8][9][10][11] This result has been supported by experiments with various polyelectrolytes interacting with oppositely charged micelles [12][13][14][15][16][17] and large dendrimers (smaller dendrimers behaving more like large counterions). 14,18 Still, discrepancies between the experimental systems and the theoretical model must be noted.…”
Section: Introductionmentioning
confidence: 76%
“…In summary, the interactions basically reduce to that between a PE and a PA. It has been observed that due to heterogeneous charge distribution found on protein surface, polyions (polyanions or polycations) selectively bind to oppositely charged surface patches of protein molecules through electrostatic interaction overcoming the repulsive interaction occurring between similarly charged surface patch and the polyion [62,67,[71][72][73]. Thus, SPB has been largely observed in protein-PE based interactions.…”
Section: Surface Patch Bindingmentioning
confidence: 99%